2021
DOI: 10.3390/genes12050747
|View full text |Cite
|
Sign up to set email alerts
|

Muscat Flavor in Grapevine: A Digital PCR Assay to Track Allelic Variation in VvDXS Gene

Abstract: The aroma of grapes and derived wines has long been one of the major traits considered in the selection of grapevine varieties through the centuries. In particular, Muscat aromatic grapes have been highly appreciated and widespread since ancient times. Monoterpenes are the key compounds responsible for the Muscat flavor. A major QTL affecting monoterpene level has been found to co-localize with the 1-deoxy-D-xylulose 5-phosphate synthase (VvDXS) gene, encoding for the 1-deoxy-D-xylulose 5-phosphate synthase en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Additionally, we found that only VvDXS was significantly correlated with linalool and total terpene concentrations, while the expression of other terpene-related genes were apparently uncorrelated with terpene accumulation in general (Figure 5). DXS is the first enzyme involved in the MEP pathway of isopentenyl-5-pyrophosphate (IPP) biosynthesis [59]. Our observation of the correlation between grape linalool content and VvDXS expression is in agreement with Battilana et al [57] and Emanuelli et al [60] (Table 5), who demonstrated the colocalization of VvDXS with the major QTL for monoterpene content positioned on chromosome 5, and indicating that VvDXS is a candidate gene for the regulation of these important grape monoterpenes.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, we found that only VvDXS was significantly correlated with linalool and total terpene concentrations, while the expression of other terpene-related genes were apparently uncorrelated with terpene accumulation in general (Figure 5). DXS is the first enzyme involved in the MEP pathway of isopentenyl-5-pyrophosphate (IPP) biosynthesis [59]. Our observation of the correlation between grape linalool content and VvDXS expression is in agreement with Battilana et al [57] and Emanuelli et al [60] (Table 5), who demonstrated the colocalization of VvDXS with the major QTL for monoterpene content positioned on chromosome 5, and indicating that VvDXS is a candidate gene for the regulation of these important grape monoterpenes.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported that terpene accumulation in grape and other plants was correlated with gene expression in the MEP pathway [17], such as VvDXS, VvDXR, VvHDR and VvGPPS [18][19][20]. Of the corresponding proteins, DXS is the first enzyme involved in the MEP pathway [21]. Battilana et al [18] and Emanuelli et al [22] reported the co-localization of VvDXS with a major quantitative trait locus (QTL) for monoterpene concentration positioned on chromosome 5 of grapevine.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have applied this technology to other objectives, such as the evaluation of gene expression or the control of edited plants. Moving toward traceability applications, Morcia et al [ 48 ] developed a digital PCR for the identification and quantification of Muscat-flavored grapes, but no example of digital PCR applied to the traceability of a specific grape variety has been proposed until now. Several DNA-based technologies are currently used for varietal genotyping [ 8 ], among them even one able to give in-the-field varietal authentication [ 49 ].…”
Section: Discussionmentioning
confidence: 99%